COVID-19, asthma, and biological therapies: what we need to know - Morais Almeida, Mario; Aguiar, Rita; Martin, Bryan; Ansotegui, Ignacio J.; Ebisawa, Motohiro; Arruda, L. Karla; Caminati, Marco; Canonica, Giorgio Walter; Carr, Tara; Chupp, Geoffrey; Corren, Jonathan; Dávila, Ignacio; et al. (2020)
Managing patients with severe asthma during the coronavirus pandemic and COVID-19 is a challenge. Authorities and physicians are still learning how COVID-19 affects people with underlying diseases, and severe asthma is not an exception. Unless relevant data emerge that change our understanding of the relative safety of medications indicated in patients with asthma during this pandemic, clinicians must follow the recommendations of current evidence-based guidelines for preventing loss of control and exacerbations. Also, with the absence of data that would indicate any potential harm, current advice is to continue the administration of biological therapies during the COVID-19 pandemic in patients with asthma for whom such therapies are clearly indicated and have been effective. For patients with severe asthma infected by SARS-CoV-2, the decision to maintain or postpone biological therapy until the patient recovers should be a case-by-case based decision supported by a multidisciplinary team. A registry of cases of COVID-19 in patients with severe asthma, including those treated with biologics, will help to address a clinical challenge in which we have more questions than answers.